Securing cyberspace : threats and challenges to NATO - Almeida, António Miguel Correia Semedo Neves (2023)
Cyberspace, and the topic of cyber, is today an issue of great importance. This thesis explores the significance of cyberspace and cyberspace security within the context of NATO and the current and future threats and challenges faced by the Alliance. In an interconnected world, cyberspace serves as a critical medium linking individuals, organizations, and vital infrastructures. However, it also presents an attractive target for malicious actors seeking to disrupt, steal information, or launch cyber-attacks. The emergence of hybrid warfare and information warfare further highlights the importance of securing cyberspace. The interconnectedness of critical infrastructure systems further emphasizes the need to protect cyberspace to ensure national security, economic stability, and public safety. As NATO operates on the principle of collective defence, strengthening cyberspace security enables the Alliance to respond collectively to cyber threats that transcend borders. Furthermore, as technology continues to advance, cyberspace security becomes even more crucial to address emerging risks and vulnerabilities. By prioritizing cyberspace security, NATO can enhance its resilience, promotes information sharing, and remain adaptable in the face of evolving cyber threats.